2022
DOI: 10.33225/jbse/22.21.663
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Inquiry-Based Chemistry Experimentation on Students’ Attitudes Towards the Teaching and Learning of Chemistry

Abstract: Students' attitude towards a subject is a key indicator of academic performance, therefore its enhancement is imperative for academic success. A sample of 328 grade eleven students was selected using cluster random sampling. Two different study groups; the experimental and control groups, were composed and exposed to the guided inquiry and demonstration methods of teaching chemistry experiments respectively. The Non-equivalent control group research design was employed with instruction lasting six weeks. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 21 publications
2
4
0
Order By: Relevance
“…Attitude directly affects behavior intention, implying that the more students develop positive attitudes toward inquiry-based teaching, the more they accept it. This result consists fairly well with the literature ( Akman and Turhan, 2017 ; Moreno et al, 2017 ; Nicol et al, 2022 ; Ye et al, 2023b ), demonstrating that attitude was a significant predictor. Therefore, in order to improve students’ acceptance of inquiry-based teaching, the key lies in changing students’ understanding of inquiry-based teaching to shape positive attitude.…”
Section: Discussionsupporting
confidence: 91%
“…Attitude directly affects behavior intention, implying that the more students develop positive attitudes toward inquiry-based teaching, the more they accept it. This result consists fairly well with the literature ( Akman and Turhan, 2017 ; Moreno et al, 2017 ; Nicol et al, 2022 ; Ye et al, 2023b ), demonstrating that attitude was a significant predictor. Therefore, in order to improve students’ acceptance of inquiry-based teaching, the key lies in changing students’ understanding of inquiry-based teaching to shape positive attitude.…”
Section: Discussionsupporting
confidence: 91%
“…This proved that the implementation of inquiry activities with the 5E model had a positive impact on students' attitude toward chemistry as a subject. These findings indicate that teaching with the 5E model influences students' attitudes on the importance of chemistry and science in general, which is in line with other studies (e.g., Aguilera & Perales-Palacios, 2020;Bezen & Bayrak, 2020;Guven et al, 2020;Guzel, 2017;Jiang & McComas, 2015;Kang & Keinonen, 2017;Lin et al, 2014;Nicol et al, 2022;Ozkul & Ozden, 2020;Potvin et al, 2017;Savelsbergh et al, 2016;Wiriani & Ardana, 2022). The positive effect of IBSE on the "affective" results such as students' attitude to learning science was also identified by Ergul et al (2011), Gibson and Chase (2002), Potvin and Hasni (2014), and Wolf and Fraser (2008).…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with numerous studies conducted using quantitative, qualitative, or mixed-methods approaches. For example, Nicol et al (2022) found similar effects of guided inquiry experimentation on students' attitudes. The findings of this study are specifically supported by Nedungadi et al's (2015) research on the effect of inquiry instruction on students' motivation and interest in chemistry.…”
Section: Discussionmentioning
confidence: 88%
“…Findings from the National Learning Assessment Policy Pilot (NLAPP) study revealed a chemistry pass rate of 14% in the 2020 West African Senior Secondary Certificate Examination. The report attributed this low pass rate to inadequate teacher preparation and inappropriate teaching methods (Nicol et al, 2022). In 2021, the results for chemistry in the West African Senior Secondary Certificate Examination showed slight improvement, with 0.47% of candidates earning a credit and 5.05% scoring in the "pass" range.…”
Section: Introductionmentioning
confidence: 99%